2014
DOI: 10.4236/ajps.2014.53037
|View full text |Cite
|
Sign up to set email alerts
|

Berberine Attenuated Aging-Accelerating Effect of High Temperature in Drosophila Model

Abstract: We have observed that berberine prolonged life span and improved viability of pupae and climbing activity of imagoes of wild-type Drosophila melanogaster maintained at 23°C. As a continuation of our studies of berberine effect on life span, we were interested to evaluate the effect of berberine of life span in flies maintained at a higher temperature (28°C) known to accelerate aging in wild type flies. Considering that genetically or pharmacologically induced deficiency of TRP conversion into KYN prolonged lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 11 publications
1
11
0
4
Order By: Relevance
“…Finally, the alkaloid polyphenol berberine activates autophagy via SIRT1 and reduces protein acetylation (Shukla et al, 2016), protecting liver function (Sun et al, 2018), exerting neuroprotective effects (Wang et al, 2017), and reducing cardiac damage (Yu et al, 2016) in rodents. Berberine was also shown to extend the lifespan of Drosophila (Navrotskaya et al, 2012). Though oral bioavailability of berberine is poor (Liu et al, 2016), several clinical studies have been or are being performed with berberine supplementation.…”
Section: Resveratrol and Other Sirt1 Activatorsmentioning
confidence: 99%
“…Finally, the alkaloid polyphenol berberine activates autophagy via SIRT1 and reduces protein acetylation (Shukla et al, 2016), protecting liver function (Sun et al, 2018), exerting neuroprotective effects (Wang et al, 2017), and reducing cardiac damage (Yu et al, 2016) in rodents. Berberine was also shown to extend the lifespan of Drosophila (Navrotskaya et al, 2012). Though oral bioavailability of berberine is poor (Liu et al, 2016), several clinical studies have been or are being performed with berberine supplementation.…”
Section: Resveratrol and Other Sirt1 Activatorsmentioning
confidence: 99%
“…It was previously observed that BBR inhibited mTOR/S6 signaling concurrent with the reduction in the level of endogenous oxidants and constitutive DNA damage response (Zhao, Halicka, Li, & Darzynkiewicz, ). BBR also prolonged lifespan and improved viability of the wild‐type Drosophila melanogaster pupae, and the climbing activity of adult insects at higher temperatures is known to accelerate aging in wild‐type flies (Navrotskaya, Oxenkrug, Vorobyova, & Summergrad, ).…”
Section: Introductionmentioning
confidence: 99%
“…The family of IDO inhibitors were identifi ed among alkaloids isolated from Berberis aristata , a herb widely used in Indian and Chinese systems of medicine (Yu et al 2010 ). One of them, berberine, improves IR in diabetic hamsters ) and diabetic patien ts (Zhao et al 2012 ;Di Pierro et al 2012 ) and prolonged life span and improved health span in Drosophila model (Navrotskaya et al 2012(Navrotskaya et al , 2014.…”
Section: Resultsmentioning
confidence: 99%